2019
DOI: 10.21674/2448-0479.53.250-256
|View full text |Cite
|
Sign up to set email alerts
|

Atividade antifúngica in vitro dos óleos essenciais Eugenia uniflora e Psidium cattleianum contra o fitopatógeno Thielaviopsis basicola.

Abstract: O fungo Thielaviopsis basicola (Berk. & Br.) Ferr é responsável por grandes perdas econômicas em diversas culturas agrícolas. O uso de óleos essenciais é uma técnica de controle alternativo de doenças fitopatogênicas. Este trabalho teve por objetivo caracterizar os compostos bioquímicos de óleos essenciais extraídos de folhas de Eugenia uniflora L (Pitanga) e Psidium cattleianum ‘Sabine (Araçá Vermelho) e avaliar se concentrações crescentes desses óleos essenciais aumentam a inibição do crescimento do fito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
1
0
0
1
Order By: Relevance
“…( E )‐Caryophyllene was the main component identified in our study, as well as in the study by Vasconcelos and colleagues, [35] but other forms were found in high abundance, such as caryophyllene, [36] caryophyllene oxide, [35] β‐caryophyllene, [32,33,37] and trans ‐β‐caryophyllene [34] . Another highly reported compound is 1,8‐cineole, [36–38] which, however, occurred only at 2.45±1.21 % in our study. In addition to these, chemotypes with a higher proportion of hydrocarbon monoterpenes have also been observed, with a higher prevalence of α‐pinene, [29,39] which did not occur in our P. cattleyanum EO.…”
Section: Resultssupporting
confidence: 84%
“…( E )‐Caryophyllene was the main component identified in our study, as well as in the study by Vasconcelos and colleagues, [35] but other forms were found in high abundance, such as caryophyllene, [36] caryophyllene oxide, [35] β‐caryophyllene, [32,33,37] and trans ‐β‐caryophyllene [34] . Another highly reported compound is 1,8‐cineole, [36–38] which, however, occurred only at 2.45±1.21 % in our study. In addition to these, chemotypes with a higher proportion of hydrocarbon monoterpenes have also been observed, with a higher prevalence of α‐pinene, [29,39] which did not occur in our P. cattleyanum EO.…”
Section: Resultssupporting
confidence: 84%
“…O uso de óleos essenciais e de antagonistas como Saccharomyces cerevisiae no tratamento de sementes contra patógenos podem contribuir para a diminuição do uso de agrotóxicos nos plantios comerciais [12,13], reduzindo os custos de produção [12].…”
Section: Introductionunclassified